Dehydroxymethyl Bromination of Alkoxybenzyl Alcohols by Using a Hypervalent Iodine Reagent and Lithium Bromide - Shibata, Ayako; Kitamoto, Sara; Fujimura, Kazuma; Hirose, Yuuka; Hamamoto, Hiromi; Nakamura, Akira; Miki, Yasuyoshi; Maegawa, Tomohiro (Synlett, 2018)
We describe the dehydroxymethylbromination of alkoxybenzyl alcohol by using a hypervalent iodine reagent and lithium bromide in F3CCH2OH at room temperature. Selective monobromination or dibromination was possible by adjusting the molar ratios of hypervalent iodine reagent and lithium bromide.
Keywords: hypervalent iodine reagent; bromination; bromoarenes; benzylic alcohol; regioselectivity